ARTIFICIAL INTELLIGENCE AND TECHNOLOGY'S REVOLUTIONARY EFFECT ON EDUCATION (Modern education and development, 2025)
This article examines how technology and artificial intelligence (AI) have a significant impact on contemporary education. It looks at how these developments are altering instructional strategies, enhancing access to educational materials, and customizing learning experiences. In order to optimize the advantages for both students and teachers, the paper also addresses the potential and difficulties brought about by this technology integration, highlighting the necessity of careful execution and ethical considerations.